VARIABILITY OF NAVICULA MUTICOPSIS VAN HEURCK (PENNATAE DIATOM) - Tsuyako KO-BAYASHI (National Institute of Polar Research, 1962)
The author investigated the variation of Navicula muticopsis van Heurck on 365 microphotographs which were collected by HIROSHI FUKUSHIMA (Assistant Professor of Botany, Yokohama Municipal University) from the East Ongul Island (in the Antarctic) on the Feb. 3, 1959. Comparatively, there are distinct differences in forms between Navicula muticopsis van Heurck var. muticopsis forma capitata Carlson and other varieties, but it is very difficult to distinguish between Navicula muticopsis van Heurck var. mutscopsis forma evoluta W. & G. S. West and forma reducta W. & G. S. West because of their typical serial forms, and so they must be regarded as an identical variation. In all varieties and forma one typical character is noticed (Navicula muticopsis van Heurck var. gausii Heiden and Kolbe forma semicruciata form), that is, the striae on one side is absent in the central part of schale, hence Navicula muticopsis van Heurck var. gausii Heiden and Kolbe forma semicruciata Heiden and Kolbe which is known for this important character should be considered a synonym of this variety. Navicula muticopsis van Heurck var. muticopsis forma capitata Carlson is slightly larger than the typical species and the structure is more rough, and so it is much diffecult to distinguish it by such a feature. Consequently, they are arranged as follows: 1. Navicula, muticopsis van Heurck var. muticopsis forma muticopsis Synonym-Navicula muticopsis van Heurck var. muticopsis forma reducta W. & G. S. West, Navicula muticopsis van Heurck var. muticopsis forma evoluta W. & G. S. West 2. Navicula muticopsis van Heurck var. muticopsis forma capitata Carlson 3. Navicula muticopsis van Heurck var. gausii Heiden and Kolbe Synonym-Navicula muticopsis van Heurck var. gausii Heiden and Kolbe forma semicruciata Heiden and Kolbe